2020
DOI: 10.1016/j.ekir.2019.11.005
|View full text |Cite
|
Sign up to set email alerts
|

A Functional Landscape of CKD Entities From Public Transcriptomic Data

Abstract: Introduction: To develop effective therapies and identify novel early biomarkers for chronic kidney disease, an understanding of the molecular mechanisms orchestrating it is essential. We here set out to understand how differences in chronic kidney disease (CKD) origin are reflected in gene expression. To this end, we integrated publicly available human glomerular microarray gene expression data for 9 kidney disease entities that account for most of CKD worldwide. Our primary goal was to demonstrate the possib… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 64 publications
2
18
0
Order By: Relevance
“…ª 2020 The Authors EMBO Molecular Medicine 12: e11021 | 2020 activities were downregulated ( Fig 8B). Comparison to the results generated from public microarray data sets of CKD patients (Tajti et al, 2019) showed that 9 out of 11 pathways (82%) were similarly regulated in our mice compared to patients. We next generated regulatory causal networks from both murine and human data sets with the tool CARNIVAL (Liu et al, 2019).…”
Section: Dn G Dn T Ht T Ht Gmentioning
confidence: 87%
“…ª 2020 The Authors EMBO Molecular Medicine 12: e11021 | 2020 activities were downregulated ( Fig 8B). Comparison to the results generated from public microarray data sets of CKD patients (Tajti et al, 2019) showed that 9 out of 11 pathways (82%) were similarly regulated in our mice compared to patients. We next generated regulatory causal networks from both murine and human data sets with the tool CARNIVAL (Liu et al, 2019).…”
Section: Dn G Dn T Ht T Ht Gmentioning
confidence: 87%
“…Although approved only for the treatment of rheumatoid and psoriatic arthritis, numerous experimental studies document that inhibition of the JAK/STAT signaling pathway can suppress inflammation and organ damage in a wide spectrum of autoimmune and inflammatory disease models including asthma, 91 giant cell arteritis, 92 ulcerative colitis, 93 chronic pancreatitis, 94 and lupus nephritis. 95,96 Human microarray gene expression data 60 reveal overexpression of many JAK/ STAT signaling pathway-related transcripts in highly inflammatory disorders such as lupus nephritis. A transcriptome analysis of chronic UA crystal nephropathy kidneys gave consistent results.…”
Section: Discussionmentioning
confidence: 99%
“…JAK/STAT Inhibition with Tofacitinib Does Not Affect Crystal Granuloma Formation and CKD Progression in Chronic UA Crystal Nephropathy Human microarray gene expression data 60 showed that the majority of inflammatory genes including STAT1, IL4R, IL13RA1, IL6ST, IL6R, IL13, and INFG, all of which are involved in JAK/STAT signaling, were expressed in most CKD entities, albeit being most prominent in highly inflammatory kidney diseases such as lupus nephritis (Figure 3, Supplemental Methods) or FSGS. 61 However, a role for JAK/ STATsignaling in crystal nephropathies is currently unknown.…”
Section: Macrophage Phenotypes In Chronic Ua Crystal Nephropathy With...mentioning
confidence: 99%
“…To integrate the included endometrial transcriptomic experiments, several steps were followed as recommended by Tajti et al (49): after being independently normalized, selected studies were joined in a unique data set, and batch effects were corrected using linear models (limma R package) (43). A relative expression value of low, medium, and high expression were established.…”
Section: Preprocessing and Integrative Analysismentioning
confidence: 99%